2000
DOI: 10.1046/j.0007-0963.2002.04713.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical preparations for the treatment of psoriasis: a systematic review

Abstract: Summary Background There is clinical uncertainty about the appropriate use of first‐line topical treatments for psoriasis. Objectives To assess the relative effectiveness and tolerability of topical treatments for psoriasis suitable for use both in primary and secondary care. Methods All major medical databases of published literature were searched electronically; references of trial reports and recent reviews were searched; authors and companies were contacted for missing data from published reports. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
14

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(127 citation statements)
references
References 86 publications
4
109
0
14
Order By: Relevance
“…This analysis indicated that relative to all the commonly used topicals studied [except for the unlicensed twice daily application of the TCF], the TCF once daily was considered to be the most efficacious treatment for plaque psoriasis since robust evidence and state of the art evidence assimilation techniques showed a higher efficacy based on PASI 75 and CFB in PASI score. The MTC observations are consistent with results of two metaanalyses that did not include the TCF, which demonstrated that the non-fixed combination of a potent topical corticosteroid plus calcipotriol was more efficacious than calcipotriol 45,46 , and in accord with an indirect unadjusted comparison which indicated that the TCF provided higher PASI 75 response rates than the non-fixed combination and other commonly used topicals 29 . There are few national clinical guidelines for the management of scalp psoriasis; the issues relating to treatment of scalp lesions are often neglected in psoriasis treatment guidelines 47 although its challenges are mentioned in the recent British Association of Dermatologists and Primary Care Dermatology Society recommendations for the initial management of psoriasis 48 .…”
supporting
confidence: 78%
“…This analysis indicated that relative to all the commonly used topicals studied [except for the unlicensed twice daily application of the TCF], the TCF once daily was considered to be the most efficacious treatment for plaque psoriasis since robust evidence and state of the art evidence assimilation techniques showed a higher efficacy based on PASI 75 and CFB in PASI score. The MTC observations are consistent with results of two metaanalyses that did not include the TCF, which demonstrated that the non-fixed combination of a potent topical corticosteroid plus calcipotriol was more efficacious than calcipotriol 45,46 , and in accord with an indirect unadjusted comparison which indicated that the TCF provided higher PASI 75 response rates than the non-fixed combination and other commonly used topicals 29 . There are few national clinical guidelines for the management of scalp psoriasis; the issues relating to treatment of scalp lesions are often neglected in psoriasis treatment guidelines 47 although its challenges are mentioned in the recent British Association of Dermatologists and Primary Care Dermatology Society recommendations for the initial management of psoriasis 48 .…”
supporting
confidence: 78%
“…One meta-analysis identified only 42 well-designed, placebo-controlled trials of topical agents for the treatment of psoriasis, with only 7 focusing specifically on scalp psoriasis. 12 Most trials only cover short-term treatment. This section briefly reviews the efficacy, safety, and convenience of the most significant available topical treatments, and comments on the quality of evidence.…”
Section: Current Treatments For Scalp Psoriasismentioning
confidence: 99%
“…Topical steroids have been the mainstays of treatment for many years. Multiple randomised controlled trials 17 (RCTs) have found that potent (e.g., mometasone [Elocon®] ointment) and very potent (e.g., clobetasol [Dermovate®]) topical steroids improve psoriasis plaques. The major limitation of these studies is their short duration, averaging only four weeks.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27] Topical Steroids. Topical steroids have been the mainstays of treatment for many years.…”
Section: Topical Therapiesmentioning
confidence: 99%